Penguatan Keterampilan Masyarakat Melalui Diversifikasi Produk Kepiting Bakau (Scylla spp.) Menjadi Nugget dan Sumpia - Handayani Handayani; Muhammad Ulat; Muh. Kasim; Asthervina Widyastami Puspitasari (Buletin SWIMP, 2021)
The low grade of mud crab catched causing market crashes. Aim of this actvities was to improve the skills of local partner in processing low grade mud crab to be more valuable. This activity was collaboration between Polytechnic KP Sorong and Conservation International using demonstration and direct instruction model through training on processing of nugget and sumpia based mud crab with 10 participants from Komplek Rimba Pala, Jalan Mandiri RT. 06, RW. 06, District Remu Selatan, Sorong City, Papua Barat Province. Post-test which part of the evaluation, it was showen an increasing in the knowledge and skill possess by local partner.